2017
DOI: 10.21059/buletinpeternak.v41i1.12980
|View full text |Cite
|
Sign up to set email alerts
|

IMPROVING PHYSICO-CHEMICAL CHARACTERISTIC AND PALATABILITY OF KING GRASS (Pennisetum hybrid) SILAGE BY INOCULATION OF Lactobacillus plantarum - Saccharomyces cerevisiae CONSORTIA AND ADDITION OF RICE BRAN

Abstract: This study was conducted to determine the effectiveness of inoculants consisted of lactic acid bacteria Lactobacillus plantarum (Lp) and yeast Saccharomyces cerevisiae (Sc) combined with the addition of rice bran on the physicochemical characteristics and palatability of king grass (Pennisetum hybrid) silage. The experiment was arranged in the randomized factorial design (3x3) consisting of the inoculants treatments (control, Lp, Lp+Sc) and the different level of rice bran addition (0, 5 and 10%) which contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…According to Rahayu et al (2017) good silage has a yellowish green or brownish green color and the silage's flavor was fresh acid as a characteristic of high lactic acid and the decay that causes silage smells of butyric, silage has a dense and soft texture and is not slimy and moldy. Treated silage has fragrant flavor compare to the control silage and silage without inoculant and WSC showed the worst flavor compare with others (Sofyan et al, 2017;Mustika and Hartutik, 2021). This is in accordance with the opinion of Despal et al (2011) which states that silage given molasses has a slightly moist texture so that it is in accordance with ideal conditions for bacterial growth.…”
Section: Physical Quality and Phsupporting
confidence: 81%
See 1 more Smart Citation
“…According to Rahayu et al (2017) good silage has a yellowish green or brownish green color and the silage's flavor was fresh acid as a characteristic of high lactic acid and the decay that causes silage smells of butyric, silage has a dense and soft texture and is not slimy and moldy. Treated silage has fragrant flavor compare to the control silage and silage without inoculant and WSC showed the worst flavor compare with others (Sofyan et al, 2017;Mustika and Hartutik, 2021). This is in accordance with the opinion of Despal et al (2011) which states that silage given molasses has a slightly moist texture so that it is in accordance with ideal conditions for bacterial growth.…”
Section: Physical Quality and Phsupporting
confidence: 81%
“…This is in accordance with the opinion of Despal et al (2011) which states that silage given molasses has a slightly moist texture so that it is in accordance with ideal conditions for bacterial growth. The palatability was influenced by taste, texture and also flavor (Sofyan et al, 2017). The result showed that silage with 10% molasses addition with 21 days ensiling times more palatable than others.…”
Section: Physical Quality and Phmentioning
confidence: 98%